1992
DOI: 10.1007/bf01108843
|View full text |Cite
|
Sign up to set email alerts
|

Parallel distributed processing and neuropsychology: A neural network model of Wisconsin card sorting and verbal fluency

Abstract: Neural networks can be used as a tool in the explanation of neuropsychological data. Using the Hebbian Learning Rule and other such principles as competition and modifiable interlevel feedback, researchers have successfully modeled a widely used neuropsychological test, the Wisconsin Card Sorting Test. One of these models is reviewed here and extended to a qualitative analysis of how verbal fluency might be modeled, which demonstrates the importance of accounting for the attentional components of both tests. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Surprisingly, there are only a handful of studies examining the reliability and validity of executive function measures, and these studies usually find low reliability and inadequate validity (Bowden et al, 1998;Humes et al, 1997;Kafer and Hunter, 1997;Miyake et al, 2000;Schnirman et al, 1998;Vandierendonck, 2000). Parks et al (1992) suggested that parallel distributed processing (PDP) models of executive function tasks may help to circumvent some of these problems with reliability and validity. It is important, however, to discuss briefly what PDP modeling is before explaining how it addresses the reliability and validity of executive function measures.…”
Section: Summary Of Qualitative and Quantitative Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, there are only a handful of studies examining the reliability and validity of executive function measures, and these studies usually find low reliability and inadequate validity (Bowden et al, 1998;Humes et al, 1997;Kafer and Hunter, 1997;Miyake et al, 2000;Schnirman et al, 1998;Vandierendonck, 2000). Parks et al (1992) suggested that parallel distributed processing (PDP) models of executive function tasks may help to circumvent some of these problems with reliability and validity. It is important, however, to discuss briefly what PDP modeling is before explaining how it addresses the reliability and validity of executive function measures.…”
Section: Summary Of Qualitative and Quantitative Reviewsmentioning
confidence: 99%
“…Subsequently, investigators produced empirical physiological data that were compatible with the psychological theories (Parks et al, 1992). Following the advent of "supercomputers" that could integrate the physiological and psychological data, PDP modeling was developed.…”
Section: Summary Of Qualitative and Quantitative Reviewsmentioning
confidence: 99%
“…Neural networks implementing such pre-existing rules have been created and demonstrated to mimic human performance (Levine & Prueitt 1989;Dehaene & Changeux 1991;Parks et al 1992;Carter 2000;Kaplan et al 2006). In these systems, the top-2 knowledge has been either hand-coded (e.g., Dehaene & Changeux 1991) or pre-trained (e.g., Carter 2000)-in either case acquisition of those rules requiring an intervention from a side of a human programmer.…”
Section: A T3-system: Anapoiesis and Abduction-the Mindmentioning
confidence: 99%
“…These tests are modeled after the Wisconsin Card Sorting test, which was designed to assess cognitive flexibility, or set-shifting, in humans (Dehaene and Changeux, 1991;Milner, 1963;Parks et al, 1992). These tests are modeled after the Wisconsin Card Sorting test, which was designed to assess cognitive flexibility, or set-shifting, in humans (Dehaene and Changeux, 1991;Milner, 1963;Parks et al, 1992).…”
Section: Working Memory: Delayed Matchingmentioning
confidence: 99%